THE DEMARCATION OF THE POWER PROBLEM FIELD IN THEORETICAL CONCLUSIONS BY H. MARCUSE - Поліщук, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This article is a study of some theoretical conclusions by H. Marcuse concerning power. Here we describe the concept of power by H. Marcuse in its relation to other issues, that important both for the classical marxists, and for the neo-marxists, in particular with the problems of rationality, totality, freedom and language. The article identifies some of the critical ideas of Marxist and Freudian concept of power in H. Marcuse’s theory, compare it with the concepts of other significant authors.